Chemical durability, electrical and dielectric properties of the ternary system (50-x)K2O–xMnO–50P2O5 phosphate glasses. (2019) - Ahmina, W.; El Moudane, M.; Shaim, A.; Zriouil, M.; Taibi, M.
Abstract: K2 O–MnO–50P2 O5 glasses containing different concentrations of MnO ranging from 20 to 35 mol % have been prepared using conventional melt-quenching technique. The amorphous nature of the samples was asserted by X–ray diffraction. The chemical durability of these glasses increases with rising MnO content. Glasses containing more than 30 mol%MnO had an excellent chemical durability. The electrical and dielectric parameters were measured in the frequency range from 10 KHz to 1 MHz in the temperature range from room temperature to 550°C. It was observed that the values of ac conductivity augment on increasing frequency. The conductivity of all the glasses increases with temperature following the Arrhenius law. Activation energy was found to increase with raise in concentration of manganese oxide and decrease with the increase in the frequency. It was also observed that the values of dielectric constant and loss factor enhance with the increase in temperature and decrease with increase in frequency in all the glasses studied. These results agree with a closer structure and act in a manner that Mn 2+ enters the glassy matrix as a network former character